Thermal environment as a parameter for urban planning - de Souza, Léa Cristina Lucas [UNESP] (Elsevier, 2007)
This paper suggests an analysis of the urban thermal environment by the development of maps in a GIS environment, rather than relying only on numerical analyses. Urban canyons in an area of a medium-sized Brazilian city were studied to demonstrate the approach. First, a computational algorithm was applied in order to allow the determination of sky view factors (SVFs) and sun-paths in urban canyons. Then, air and surface temperatures in 40 measurement points were collected within the study area. The creation of thermal maps for the whole neighborhood was possible due to a statistical treatment of the data, through the interpolation of values. All data could then be spatially cross-examined. In addition, thermal comfort maps for summer and winter were generated. This methodology allowed the identification of thermal tendencies within the neighborhood, which can be useful in the definition of guidelines for urban planning purposes. © 2007 International Energy Initiative, Inc.